Isoquercitrin from Argemone platyceras inhibits carbachol and leukotriene D4-induced contraction in guinea-pig airways - Fernandez, J.; Reyes, R.; Ponce, H.; Oropeza, M.; Vancalsteren, M.R.; Jankowski, C.; Campos, M.G.
Argemone platyceras is used in Mexico as a remedy for cough, bronchitis and pneumonia. The present study was performed to investigate the pharmacological anti-asthmatic properties of Argemone platyceras on airways and to identify its active principles. Methanol extracts of leaves and flowers, subsequent organic and aqueous extraction phases, and silica gel chromatography fractions were assayed on the carbachol-induced response, and/or on ovalbumin antigenic challenge, and on leukotriene D4-induced response of tracheae from sensitized and non-sensitized guinea-pigs. Methanol extracts, ethyl-acetate phase, and its fractions 6 and 7 inhibited the carbachol-induced contractile esponse. Isoquercitrin and rutin were the main compounds found in fractions 6 and 7 respectively. Isoquercitrin (fraction 6)abolished the response to ovalbumin, and decreased the contractile response to leukotriene D4. Because of its effect on carbachol-induced contractile response, on the late-phase response to ovalbumin, and on leukotriene D4-induced contractile response, isoquercitrin might be highly useful in treatment of asthma
Keywords: ISOQUERCITRIN; RUTIN; ASTHMA; CARBACHOL; ARGEMONE PLATYCERAS; ANTIGEN CHALLENGE; ANTI-ASMATHIC PROPERTIES; ANTI-LEUKOTRIENE ACTION